2011
DOI: 10.1111/j.1365-2966.2011.18509.x
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of solar-like oscillations of clusters simulated by stellar population synthesis

Abstract: Using a stellar population‐synthesis method, we studied the distributions of νmax and Δν of simulated clusters with various ages and metallicities. Except for the confirmed peak (RC peak) of Δν of red‐clump (RC) stars, i.e. core helium‐burning stars, one sees a gap and a main‐sequence (MS) peak in the distributions of νmax and Δν of young clusters. The gap corresponds mainly to the Hertzsprung‐gap phase of evolution. The RC peak is caused by the fact that the radii of many RC stars near the zero‐age horizontal… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 50 publications
0
6
0
Order By: Relevance
“…Furthermore, it has been identified that non‐uniform distributions of ν max and Δν of red giants result from red‐clump [core helium‐burning (CHeB)] stars (Miglio et al 2009; Huber et al 2010; Mosser et al 2010; Yang et al 2010; Hekker et al 2011b). The dominant peak in the distributions of ν max and Δν, which is located around 30 and 4 μHz for ν max and Δν, respectively, is mainly composed of stars that are close to the zero‐age horizontal branch (ZAHB: Yang et al 2010, 2011a). Stars with ν max > 40 μHz are mainly red‐clump stars with mass larger than 2.0 M ⊙ (Huber et al 2010).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, it has been identified that non‐uniform distributions of ν max and Δν of red giants result from red‐clump [core helium‐burning (CHeB)] stars (Miglio et al 2009; Huber et al 2010; Mosser et al 2010; Yang et al 2010; Hekker et al 2011b). The dominant peak in the distributions of ν max and Δν, which is located around 30 and 4 μHz for ν max and Δν, respectively, is mainly composed of stars that are close to the zero‐age horizontal branch (ZAHB: Yang et al 2010, 2011a). Stars with ν max > 40 μHz are mainly red‐clump stars with mass larger than 2.0 M ⊙ (Huber et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the values of νmax and ∆ν of red giants of clusters NGC 6811, NGC 6819, and NGC 6791 have also been extracted by Stello et al (2010a) and Hekker et al (2011a). For an ensemble of stars, the νmax and ∆ν can be applied to investigate many interesting questions about the Galaxy or stellar clusters (Miglio et al 2009(Miglio et al , 2012Miglio 2011;Yang et al , 2011aHuber et al 2010;Mosser et al 2010;Hekker et al 2011a,b;Stello et al 2010aStello et al ,b, 2011. These studies advanced our understanding of the theory of stellar structure and evolution.…”
Section: Introductionmentioning
confidence: 99%
“…Then, just as the case of 1.0 M ⊙ models, the rotational mixing begins to play a dominant role. The rotating models exhibit a higher effective temperature and an approximately equal luminosity compared to the non-rotating ones when they evolved into the same evolutionary state [for instance the beginning of the MS hook (Yang et al 2011a) in the HR diagram]. Moreover, for the star with M = 1.4 M ⊙ , Fig.…”
Section: Resultsmentioning
confidence: 88%
“…Asteroseismology has proved to be a powerful tool for determining fundamental star parameters, diagnosing internal structures of stars, and probing physical processes in stellar interiors (Eggenberger et al 2005;Yang & Bi 2007b;Stello et al 2009;Christensen-Dalsgaard & Houdek 2010;Yang et al 2010Yang et al , 2011aYang et al , 2012Silva Aguirre et al 2011Liu et al 2014;Chaplin et al 2014;Metcalfe et al 2014;Guenther et al 2014).…”
Section: Introductionmentioning
confidence: 99%